Interference Effect in Electron Emission in Heavy Ion Collisions with H2 Detected by Comparison with the Measured Electron Spectrum from Atomic Hydrogen - Misra, Deepankar; Kadhane, U.; Singh, Y. P.; Tribedi, L. C.; Fainstein, P. D.; Richard, P. (My University, 2004)
Direct evidence of the interference effect in the electron emission spectra from ionization of molecular hydrogen in collisions with bare C and F ions at relatively low collision energies is presented. Oscillations due to the interference are deduced by comparing the measured double differential cross sections of the electrons emitted from molecular hydrogen to those emitted from atomic hydrogen, rather than using the calculated cross sections for H as in a previous report. We believe these experimental data provide stronger support for the evidence of the interference effect. We show that it is not only a feature of very high energy collisions, but also a feature to be observed in relatively lower energy collisions.